Corporate Codes of Ethics, National Culture, and Earnings Discretion: International Evidence - Chen, Chu (Journal of business ethics, 2018)
This study examines the role of codes of ethics in reducing the extent to which managers act opportunistically in reporting earnings. Corporate codes of ethics, by clarifying the boundaries of ethical corporate behaviors and making relevant social norms more salient, have the potential to deter managers from engaging in opportunistic financial reporting practices. In a sample of international companies, we find that the quality of corporate codes of ethics is associated with higher earnings quality, i.e., lower discretionary accruals. Our results are confirmed for a subsample of firms more likely to be engaging in opportunistic reporting behavior, i.e., firms that just meet or beat analysts’ forecasts. Further, codes of ethics play a greater role in reducing earnings management for firms in countries with weaker investor protection mechanisms. Our results suggest that corporate codes of ethics can be a viable alternative to country-level investor protection mechanisms in curbing aggressive reporting behaviors.